2017
DOI: 10.1021/acscatal.7b01543
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Organo- and Biocatalytic Process for the Asymmetric Transformation of Alcohols into Amines in Aqueous Medium

Abstract: A hybrid organo-and biocatalytic system for the asymmetric conversion of racemic alcohols into amines was developed. Combining an organocatalyst, AZADO, an oxidant, NaOCl, and an enzyme, transaminase, we implemented a one-pot oxidation-transamination sequential process in aqueous medium.The method showed broad substrate scope and was successfully applied to conventional secondary alcohols and sterically hindered -substituted cycloalkanols, where a highly stereoselective dynamic asymmetric bioamination enable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 64 publications
(38 reference statements)
1
31
0
Order By: Relevance
“…2-Keto-3-deoxy sugar acids are interesting building blocks for bio-based chemicals because theyc an be derived from sugar.S ieber et al suggested an ew route for their synthesis by the coupling of the chemical oxidation of sugars with an enzymatic dehydration step. [30] Similar to the work of Gonzalez-Sabína nd co-workers( see above), [24] the synthetic challenge was to achieve an oxidation under mild reaction conditions and the combination with an enzymatic step without intermediary steps for product recovery.S ieber and coworkers chose ag old catalyst for the oxidation (Scheme 3d). Both reactions proceed in aqueous systems.…”
Section: Concurrent Cascades In Organic Mediamentioning
confidence: 98%
See 1 more Smart Citation
“…2-Keto-3-deoxy sugar acids are interesting building blocks for bio-based chemicals because theyc an be derived from sugar.S ieber et al suggested an ew route for their synthesis by the coupling of the chemical oxidation of sugars with an enzymatic dehydration step. [30] Similar to the work of Gonzalez-Sabína nd co-workers( see above), [24] the synthetic challenge was to achieve an oxidation under mild reaction conditions and the combination with an enzymatic step without intermediary steps for product recovery.S ieber and coworkers chose ag old catalyst for the oxidation (Scheme 3d). Both reactions proceed in aqueous systems.…”
Section: Concurrent Cascades In Organic Mediamentioning
confidence: 98%
“…Gonzáles‐Sabin and co‐workers successfully applied a non‐stereoselective oxidation using the organocatalyst 2‐azaadamantane N ‐oxyl (AZADO) together with NaOCl as mediator for the oxidation of a series of 2‐(benzyloxy)cycloalkanoles (Scheme e). The reaction conditions were mild enough to be compatible with the subsequent reductive amination by several ( S )‐selective and ( R )‐selective transaminases . Interestingly, the tendency of several 2‐(benzyloxy)cycloalkanones to undergo spontaneous racemization under slightly basic conditions allowed for the use of stereoselective amination to establish a dynamic kinetic resolution, giving rise to a series of diastereomerically pure 2‐(benzyloxy)cycloalkylamines in high isolated yield, good to excellent diastereomeric purity (up to 98:2), and very high optical purity (>99 % ee ).…”
Section: Chemoenzymatic Cascade Reactionsmentioning
confidence: 99%
“…[15] For instance, Rebolledo and co-workers have reported the catalytic chemical oxidation of 1arylpropan-2-ols mediated by AZADO to produce the corresponding 1-arylpropan-2-ones, which were later subjected to asymmetric biotransamination using ATAs. [16] Multienzymatic strategies for the synthesis of optically active 1-arylpropan-2-amines from alcohols rely on the combination of two stereocomplementary alcohol dehydrogenases (ADHs) for the oxidation of racemic 1-arylpropan-2-ols to subsequently perform the biotransamination reaction [17] or the reductive amination catalysed by an AmDH. [18] Alternatively, a redox-neutral cascade has been described starting from racemic 1-phenylpropan-2-ol based on the use of a single non selective ADH for alcohol oxidation and subsequent reductive amination employing the reductive aminase from Aspergillus oryzae.…”
Section: Introductionmentioning
confidence: 99%
“…[5] UCB pharma has developed several synthetic routes for the preparation of the 2-oxo-pyrrolidine derivative, [6][7][8] however, these exclusively chemical methods come along with poor stereoselectivity and hence elaborate chromatography steps in order to obtain the far more active (2S,4R)-stereoisomer in pure form. Interestingly, despite of their popularity for the synthesis of chiral amines used for APIs and their successful application also on industrial scale, [24][25][26][27][28][29][30][31] transaminases (TA) [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] have not yet been considered as the biocatalyst of choice to prepare key intermediates of Pregabalin and Brivaracetam by deracemisation of the corresponding aldehydes. This process has been improved in terms of yield and economical aspects by replacing chemical resolution by a lipasecatalysed one.…”
Section: Introductionmentioning
confidence: 99%